Pyoderma gangrenosum mimicking granulomatosis with polyangiitis: case report and riview of the literature - Olga Yu. Olisova; Natalia P. Teplyuk; Olga V. Grabovskaya; Diana T. Kusraeva; Lyailya N. Kayumova; Anna E. Bobkova; Vladimir A. Varshavsky; Lyudmila F. Komleva; Ekaterina V. Petrenko; Ksenia Yu. Bobrova (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
Pyoderma gangrenosum is an autoinflammatory neutrophilic dermatosis. Diagnosis of the disease remains a difficult task to date, due to the lack of a standard of examination and differential diagnostic signs. The primary elements in the development of PG may be papules, pustules or bullae the dissection of which subsequently leads to the formation of ulcers with irregular, violaceous, undermined borders. In rare cases, the diagnosis of the disease can also be complicated by the rapid development of internal organs damage symptoms, which must be regarded as extracutaneous manifestations of PG. Extracutaneous lesions can occur before, during or after the appearance of skin rashes, and the detection of sterile neutrophil infiltrates in the defeat of internal organs confirm the concept of PG as a multisystemic disease. The presented case of a rare course of PG with multiple skin lesions and extracutaneous manifestations, simulating systemic vasculitis, emphasizes the importance of a detailed examination of patients in order to make a correct diagnosis and prescribe timely adequate treatment.